Development of a novel tongue biofilm index using bacterial biofluorescence - Sol Park; Eun-Song Lee; Areum Kim; Hyo-Jung Kim; Joo-Young Lee; Sang-Kyeom Kim; Hoi-In Jung; Baek-Il Kim (Scientific Reports)
Abstract Conventional methods for assessing tongue bacterial biofilms have low inter-examiner reliability due to visualization challenges. This study aimed to develop and assess a novel Tongue Biofilm Fluorescence Index (TBFI) for the accurate detection and objective evaluation of the quantitative and qualitative characteristics of tongue biofilms at the chairside. Data were collected from 81 elderly individuals (n = 162 images). Qraycam captured white-light and fluorescence images of the dorsal tongue, and two examiners assessed tongue coating (TC) using the TBFI. The TBFI was calculated based on biofilm intensity and coverage (0–2 scale). Inter-examiner agreement (Kappa) was compared with the Winkel’s Tongue Coating Index (WTCI) and the Oho Index. Validity was evaluated through correlations with hydrogen sulfide (H₂S) and methyl mercaptan (CH₃SH) levels. TBFI demonstrated the highest inter-examiner reliability (TBFI, κ = 0.752; WTCI, κ = 0.317; Oho Index, κ = 0.496), particularly for thickness rating (agreement rate: TBFI, 96.3%; WTCI, 76.5%; Oho Index, 79.6%). H₂S and CH₃SH concentrations showed significant positive correlations with all three indices, with the highest correlation observed between H₂S and TBFI (TBFI, r = 0.369; WTCI, r = 0.304; Oho Index, r = 0.308; p < 0.01). Furthermore, H₂S levels increased significantly with higher TBFI scores (p < 0.0001). TBFI shows enhanced reliability and validity, supporting its clinical potential.